MANAJEMEN PROYEK SISTEM INFORMASI PERANCANGAN APLIKASI GOSHIP BERBASIS MOBILE ANDROID - Ahadi, Rosari Zakia; Aditya, Ngakan Made Bayu; Nasution, Satria; Paramarta, Vip (JURNAL BISNIS KOLEGA, 2023)
Sea crossing transportation is a link for community activities in Balikpapan Bay by ordering speedboats and klotok boats. The Goship application is an information system in the form of an android-based application that is used to facilitate sea crossing transportation services to run effectively and efficiently. The Goship application offers direct booking services between drivers and passengers only via smartphones in the application. . Passengers who are going to cross can be made easier by simply using the application on their smart phone by clicking GO and can order the type of ship and the desired destination. The estimated time for designing and making this program is about four months. It is estimated that the costs incurred in the process of this program are around Rp. 2,600,000, -. the energy needed in making this program is two people and one programmer.